Situation in Bilbao : Memorandum of interview : telephone conversation - Lizaso, Jose I. de ; Eden, Anthony, Earl of Avon, 1897-1977; Citrine, Walter, 1887-1983
1937-06-19 016a-0018-005 292/946/16a/20(v)